Theoretical studies on aluminum trialkoxide-initiated lactone ring-opening polymerizations: Roles of alkoxide substituent and monomer ring structure - Jitonnom J. (2017)
© 2016 Elsevier B.V. Four aluminum (III) trialkoxides, namely, Al(III) ethoxide (1), Al(III) isopropoxide (2), Al(III) tert-butoxide (3), and Al(III) sec.-butoxide (4), have been evaluated their efficiency as initiators for bulk ring-opening polymerizations (ROP) of some lactones (γ-butyrolactone (GBL), γ-valerolactone (GVL), δ-valerolactone (VL) and ε-caprolactone (CL)). The influences of the initiator's alkoxide substituent and monomer ring structure on the initiating activity and mechanism of ROP were computationally analyzed by means of density functional theory (DFT) method. Upon the activation energies, the relative activities of the initiators toward CL ROP follow the trend 4 > 2 > 3 > 1, which were also confirmed by experiment. All initiators were found to follow the coordination-insertion mechanism. It was shown that 2 and 4 were efficient initiators for the reaction and the calculations demonstrate that their branch substituents play a key role in stabilizing intermediates and transition states that leads to lower reaction energies and activation barriers. The rate-determining step of the initiation was the formation of penta-O-coordinated Al, and their computed activation energies (24.5–34.8 kcal/mol) were in agreement with available kinetic data.